2018
DOI: 10.7717/peerj.5982
|View full text |Cite
|
Sign up to set email alerts
|

Classification of the glioma grading using radiomics analysis

Abstract: BackgroundGrading of gliomas is critical information related to prognosis and survival. We aimed to apply a radiomics approach using various machine learning classifiers to determine the glioma grading.MethodsWe considered 285 (high grade n = 210, low grade n = 75) cases obtained from the Brain Tumor Segmentation 2017 Challenge. Manual annotations of enhancing tumors, non-enhancing tumors, necrosis, and edema were provided by the database. Each case was multi-modal with T1-weighted, T1-contrast enhanced, T2-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(127 citation statements)
references
References 48 publications
2
105
0
8
Order By: Relevance
“…Através da mesma base de dados aqui aplicada, um modelo produzido por [Cho et al 2018] utilizou o algoritmo RF com 5 atributos radiomics de forma e textura para resolver o mesmo problema de classificação, atingindo valores de AUC, acurácia, sensibilidade e especificidade de 0,9213, 0,8877, 0,9429 e 0,7333, respectivamente. Apesar de ter apresentado melhores resultados se comparado ao nosso modelo com RF, obteve um desempenho inferior aos resultados fornecidos por nosso modelo com SVM.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Através da mesma base de dados aqui aplicada, um modelo produzido por [Cho et al 2018] utilizou o algoritmo RF com 5 atributos radiomics de forma e textura para resolver o mesmo problema de classificação, atingindo valores de AUC, acurácia, sensibilidade e especificidade de 0,9213, 0,8877, 0,9429 e 0,7333, respectivamente. Apesar de ter apresentado melhores resultados se comparado ao nosso modelo com RF, obteve um desempenho inferior aos resultados fornecidos por nosso modelo com SVM.…”
Section: Resultsunclassified
“…Trabalho AUC Acurácia Sensibilidade Especificidade N o de atributos [Zacharaki et al 2009] 0,896 0,878 0,846 0,955 24 [Zhang et al 2017] 0,960 0,960 --50 [Cho and Park 2017] 0,887 0,898 0,889 0,907 16-34 [Chen et al 2018] 0,960 0,913 0,913 -25 [Cho et al 2018]* 0,921 0,888 0,943 0,733 5 Método proposto 0,926 0,902 0,962 0,733 47 * Trabalhos com a mesma base de dados aqui utilizada. bela 3 compara resultados obtidos em alguns trabalhos anteriores com os atingidos pela metodologia proposta.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…It is observed that VolumeNet performed the best on the holdout dataset, achieving 7% improvement in the accuracy as compared to state-of-the-art method 38 using the same dataset. Note that cross-validation was used in the compared models 37,38 for evaluating performance, with training done on a part of the same data on whose holdout portion testing was evaluated. On the other hand, we trained our models on a different dataset (from TCIA) and tested it on the BraTs dataset.…”
Section: Case Study-a: Classification Of Low/high Grade Gliomasmentioning
confidence: 95%
“…Muitos estudos recentes utilizaram atributos radiomics baseados em imagens por ressonância magnética para lidar com o problema de classificação de gliomas, fundamentando-se na ideia de que gliomas de graus mais elevados tendem a apresentar uma estrutura mais heterogênea [8] e utilizando a extração de características de textura e forma para mensurar tal heterogeneidade [13,14,15,16,17,18].…”
Section: Estrutura Do Trabalhounclassified